Pengembangan Taman Balekambang sebagai Taman Kota Cyber dengan Pendekatan Arsitektur Regionalisme - Wibowo, Adesta Ari, Rini Hidayati, ST, MT, Yayi Arsandrie, ST, MT (2015)
Cyber city is one of the modern city concept based on information technology and modern building which has now been widely applied in a number of major cities around the world. This is a logical consequence of the growing need for people who want to access information and communicate easily and quickly. After a fairly long proclaimed itself as a city of culture, Solo now confirms a new utopia that is becoming the city of cyber (cyber city). The declaration of a big dream that was held on July 30, 2008 and which was marked by the action of browsing the internet together in the city walk along Jalan Slamet Riyadi. Governance that utilize technological assistance would be more effective than government run only by human manual labor. If viewed from the concept of cyber city, Balekambang Park could be a reinforcement of the concept of cyber Solo city with an assessment of a variety, but when viewed from most of today feasibility Balekambang park quite alarming. Unsuitable Balekambang Park currently visible from the facilities and arrangements which have been damaged and no longer maintained. Currently Balekambang park development and management needed to restore both Balekambang park as a green open space properly. From the above discussion it can be concluded that the development Balekambang park is needed in the context of the development of information technology is balanced with modern technologies in the form of buildings and supporting facilities as well as the realignment of Park Balekambang as a viable green open spaces. This development can not be separated from the standpoint of local knowledge so that development takes reference from reginoalisme architecture.